Vulvar lipoma: a Case Report - Yousif Ahmed, Rami (Saudi Journal of Obstetrics and Gynecology, 2022)
Case Report and literature review We reported a case of 29 years old para two patient who was presented with painful left labial mass for 3 years , a physical examination revealed freely mobile left labial tender cystic mass . A differential diagnosis of vulvar lipoma , smooth muscle neoplasm , inclusion cyst , Bartholin cyst and epidermal cyst had been made .The patient underwent surgical excision; The mass was easily separated from the surrounding tissue, and was removed completely from its capsule. The histopathological examination revealed Single firm discoid shape mass measure 5x4x2 cm delicate capsule brown color homogenous yellow cut section , outer surface is coated black by indian ink , partialy submitted 4 cassettes diagnosis was fibrolipoma